Palliative care education in neonatal units: impact on knowledge and attitudes. Issue 2 (14th December 2012) - Twamley, Katherine; Kelly, Paula; Moss, Rebecca; Mancini, Alexandra; Craig, Finella; Koh, Michelle; Polonsky, Reen; Bluebond-Langner, Myra
Abstract : Objective: To facilitate improved and earlier access to palliative care for babies, a 4-h workshop on the principles, practice and resources in palliative care was delivered in 21 neonatal units across London. This paper assesses the impact of these workshops. Design: As part of mixed methods, processual evaluation of a series of education workshops, a pre and post survey instrument was developed, consisting of open and closed questions assessing knowledge of services and attitudes towards palliative care. Before and after each workshop attendees were invited to complete the survey. Setting: Neonatal units in hospitals across London, including examples of intensive care, high dependency and special care units. Results: 331 healthcare professionals attended the sessions, and 264 (80%) completed questionnaires. The majority of attendees were experienced neonatal nurses working in neonatal intensive care  (61% more than 7 years) but with limited experience of palliative care services. Over 79% of respondents reported that the workshop completely met their learning needs. Post-session 80% of respondents felt confident referring to palliative care services, compared with 46% before (p<0.001). Analysis of open and closed text responses revealed a shift in attitude after the sessions from a focus on dying/end-of-life, towards integrating palliative care as part of a holistic treatment plan. Conclusions: A short (half day), locally delivered workshop can change attitudes and increase knowledge in neonatal staff. Such a workshop can serve as a first step in facilitating access to and utilisation of a variety of palliative care services.